SHM_415482_HST_3D Porphyry Double-Edged Shaft Hole Axe - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Double-Edged Shaft Hole Axe of porphyry from the Swedish Middle Neolithic, collected in the field from Nygård in Buttle parish, Gotland, Sweden and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=414

Link to Sök I Samlingarna

https://samlingar.shm.se/object/A527C2E2-6E60-45F0-BFDB-CB7D195794F2
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; 3D Model; Museum Object; Dynamic Collections; Swedish Middle Neolithic; Nygård; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi